Serum Leptin, Obestatin, and Ghrelin Levels and Gastric Emptying Rates of Liquid and Solid Meals in Non-obese Rats with Roux-en-Y Bypass Surgery or Prosthesis Placement: Implications for the Role of Vagal Afferents - YEGEN, BERRAK; YEGEN, ŞEVKET CUMHUR; ÖZDEMİR KUMRAL, ZARİFE NİGAR (SPRINGER, 2017)
Background The present study aimed to investigate the effects of Roux-en-Y gastric bypass (RYGB) and prosthesis placement on gastric emptying rate in conjunction with serum ghrelin-obestatin-leptin responses in non-obese rats with intact or denervated afferent innervation. Methods Under anesthesia, male Sprague-Dawley rats underwent either sham operation, RYGB, prosthesis, and/or Gregory cannula placement. Three weeks later, liquid or solid gastric emptying tests were performed and serum ghrelin, leptin and obestatin levels were measured. Results Both prosthesis placement and RYGB surgery delayed non-nutrient liquid emptying; while solid nutrient emptying was delayed only by RYGB. Nutrient-dependent (acid, hyperosmolal and peptone) delay in liquid emptying was abolished in rats with prosthesis. By vagal afferent denervation, delayed liquid emptying was abolished, while solid emptying was further delayed in rats with prosthesis. Ghrelin and obestatin levels were depressed in prosthesis-placed rats, but RYGB surgery had no impact on both levels. Leptin level was elevated in solid-food-given rats with prosthesis, but not changed in RYGB group, while it was reduced following liquid meal. All the changes observed in ghrelin, obestatin, or leptin levels in response to meal ingestion were reversed with vagal afferent denervation. Conclusions Both RYGB and prosthesis placement had delaying effects on gastric emptying rate of non-obese rats. Our results indicate that the short-term changes in gastric motility and hormone responses induced by volume reduction are reversed by afferent denervation, suggesting that sparing the vagal innervation could be essential for reaching optimum motility and hormone changes expected after bariatric surgery.
Keywords: Roux-en Y bypass; Prosthesis; Vagal afferents; Liquid emptying; Solid emptying; Gregory cannula; BODY-MASS INDEX; SLEEVE GASTRECTOMY; WEIGHT-LOSS; INTRAGASTRIC BALLOON; SURGICAL-TREATMENT; BARIATRIC SURGERY; METABOLIC SURGERY; PLASMA GHRELIN; OBESE; INHIBITION